Aortopulmonary fistula following mitral valve replacement: a case report - Ziebell, Nágila Simon; Perin, Luiz Felipe; Rossi Filho, Raul; Horowitz, Estela Suzana Kleiman; Vieira, José Luiz da Costa; Caovilla, Fábio Vieira; Sarmento Leite, Rogerio Eduardo Gomes (Frontiers in Cardiovascular Medicine, 2025)
Acquired aortopulmonary fistula is a rare condition that may cause heart failure symptoms secondary to high-output pulmonary overload. We report an unusual case of an aortopulmonary fistula secondary to an aortic injury sustained during mitral valve replacement, which was identified during follow-up because of recurrent heart failure symptoms and repeated hospital admissions. Multimodality imaging enabled precise characterization of the fistula. After a Heart Team discussion, percutaneous closure was selected as the preferred treatment strategy. Based on the assessment of the trajectory and morphology of the fistula, a patent ductus arteriosus (PDA) occluder was chosen. Although the ostium of the fistula was challenging to identify, successful closure was achieved using the PDA occluder.